Safety and efficacy of the HIV-1 attachment inhibitor prodrug fostemsavir in heavily treatment-experienced individuals: week 96 results of the phase 3 BRIGHTE study. Issue 11 (November 2020) - Lataillade, Max; Lalezari, Jacob P; Kozal, Michael; Aberg, Judith A; Pialoux, Gilles; Cahn, Pedro; Thompson, Melanie; Molina, Jean-Michel; Moreno, Santiago; Grinsztejn, Beatriz; Diaz, Ricardo S; Castagna, Antonella; et al.
Summary: Background: Fostemsavir, a prodrug of the first-in-class attachment inhibitor, temsavir, is indicated for heavily treatment-experienced individuals with multidrug-resistant HIV-1. We previously reported superior efficacy of fostemsavir versus placebo in the randomised cohort of the BRIGHTE study after 8-day functional monotherapy (primary endpoint); here we report planned interim analyses through week 96. Methods: BRIGHTE (NCT02362503 ) is an ongoing multicentre, two-cohort, phase 3 trial, done at 108 centres in 22 countries. We enrolled heavily treatment-experienced adults (≥18 years) failing antiretroviral therapy (HIV-1 RNA ≥400 copies per mL) into two cohorts: the randomised cohort, in which patients with one or two fully active antiretrovirals remaining received oral fostemsavir (600 mg twice a day) or placebo in combination with their failing regimen for 8 days, followed by fostemsavir plus optimised background therapy; or the non-randomised cohort, in which patients with no remaining antiretroviral options received oral fostemsavir (600 mg twice a day) plus optimised background therapy from day 1. Endpoints for the week 96 interim analyses included the proportions of participants with plasma HIV-1 RNA of less than 40 copies per mL, changes from baseline in CD4 cell counts, and the frequency of adverse events, adverse events leading to discontinuation, and deaths. The intention-to-treat exposed population and the safety population both included all participants who received at least one dose of study treatment. The response rates (proportion of participants with HIV-1 RNA <40 copies per mL) in the intention-to-treat exposed population were calculated via snapshot analysis at weeks 24, 48, and 96. Findings: Between Feb 23, 2015, and Aug 11, 2016, 371 participants were enrolled and treated, of which 272 participants were in the randomised cohort and 99 in the non-randomised cohort. 320 (86%) of 371 reported a history of AIDS. In the randomised cohort, rates of virological suppression (HIV-1 RNA <40 copies per mL) increased from 53% (144 of 272) at week 24 to 60% (163 of 272) at week 96. Response rates in the non-randomised cohort were 37% (37 of 99) at week 24 and week 96. Mean increases in CD4 counts from baseline at week 96 were 205 cells per μL (SD 191) in the randomised cohort and 119 cells per μL (202) in the non-randomised cohort. Mean CD4/CD8 ratio increased from 0·20 at baseline to 0·44 at week 96 in the randomised cohort. Few adverse events led to discontinuation (26 [7%] of 371). 12 (4%) of 272 people in the randomised cohort and 17 (17%) of 99 in the non-randomised cohort died; the median baseline CD4 count for participants who died was 11 cells per μL. Interpretation: In heavily treatment-experienced individuals with advanced HIV-1 disease and limited treatment options, fostemsavir-based antiretroviral regimens were generally well tolerated and showed a distinctive trend of increasing virological and immunological response rates through 96 weeks; these findings support fostemsavir as a treatment option for this vulnerable population. Funding: ViiV Healthcare.